Penile Reconstruction in Aphallia: Modification of the De Castro Technique With Large Tissue Expander - Joanna Chen, BA; Catherine H. Bautista, BS; Ashraf Patel, MD; Mackenzie M. French, MD; Anna Mienko, BS; Anthony J. Schaeffer, MD, MPH; M. Chad Wallis, MD; Barbu Gociman, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2025)
Summary:. Aphallia is an exceedingly rare congenital malformation. The condition is the result of a sporadic anatomic anomaly during fetal development in a 46, XY male patient with otherwise normal functioning testes and male sexual hormone metabolism. Neophallus reconstruction using the De Castro phalloplasty technique is currently the most accepted treatment modality for this condition. However, most case reports in the literature do not use tissue expansion. To achieve a larger neophallus and possibly decrease the need for secondary phalloplasty postpuberty, tissue expansion should be a standardized adjunct to the De Castro procedure in the management of all patients with congenital aphallia.